Altitudinal vegetation belts in the high-Andes of central Chile (33°S) Pisos altitudinales de vegetación en los Andes de Chile central (33°S) - Lohengrin A. Cavieres; Alejandro Peñaloza; Mary Kalin Arroyo (Revista Chilena de Historia Natural, 2000)
The limits of alpine vegetation belts have been established mainly based on physiognomic criteria. However, a more objective approach for fixing limits of vegetation belts are methods based on species composition and relative abundance of each species. While these methods are more time consuming, they are more detailed and permit the detection of physical factors affecting the limits of vegetation belts. In this paper we: 1) describe the altitudinal changes of vegetation above timberline, 2) compare vegetation belts defined with physiognomy and two floristic methods (a qualitative one based on altitudinal changes in species composition, and a quantitative one based on changes in dominant species); and 3) detect some environmental factors responsible for the altitudinal distribution of alpine vegetation between 2100 and 3700 masl in the Andes of Santiago, central Chile (33°S). There was a complete agreement between the different methods in delimiting the subalpine belt. However, in the lower alpine belt (the cushion's belt) floristic methods subdivided it in 2-3 sub-belts. In the floristic methods, elevations 3500-3700 that formed the higher alpine belt segregated in separate ways because they have no species in common. Physiognomic descriptions lose relevant information about species distribution, especially at higher elevations. Mean annual temperature and nitrogen content of soil are the main environmental factors affecting the altitudinal limits of vegetation belts in the central Chilean Andes La delimitación de los pisos altitudinales de vegetación andina se ha basado principalmente en criterios fisionómicos. Sin embargo, un criterio más objetivo para la delimitación es usar métodos basados en la composición y abundancia relativa de las especies presentes. Mientras estos métodos requieren de un mayor esfuerzo de muestreo, son más detallados y permiten detectar factores físicos involucrados en la delimitación altitudinal de la vegetación. Los objetivos de este articulo son: 1) describir los cambios altitudinales de la de vegetación por sobre el límite arbóreo, 2) comparar la delimitación de los pisos de vegetación usando fisionomía y métodos floristicos (uno cualitativo basado en cambios en la composición de especies, y otro cuantitativo basado en cambios en la abundancia relativa de las especies); y 3) detectar algunos factores medioambientales responsables de los patrones de distribución altitudinal de la vegetación entre los 2.100 y 3.700 msnm en los Andes de Santiago, Chile central (33°S). Se encontró una completa concordancia entre los diferentes métodos en delimitar el piso subandino. Sin embargo, en el piso andino inferior (el piso de los cojines) los métodos florísticos lo subdividieron en 2-3 sub-pisos. Las altitudes 3.500-3.700 m que forman el piso andino superior segregaron en forma separada en los métodos florísticos ya que no tienen especies en común. En consecuencia, la descripción fisonómica pierde información relevante sobre la distribución de las especies, especialmente a mayores altitudes. La temperatura media anual y el contenido de nitrógeno del suelo fueron los principales factores medioambientales involucrados en la delimitación altitudinal de la vegetación de los Andes de Chile central